Optimization of the independent work of students-philologists of credit-modular system of organizing the educational process (Pedagogy of Higher and Secondary Education, 2012)
Bondar L. Optimization of the independent work of students-philologists of credit-modular system of organizing the educational process.This article considers the ways to optimization of students’ independent work in the modern teaching of high school, its substantial characteristics of an important component of the educational process are completed here.
Keywords: independent work; credit-module system of organizing the educational process; a model of personality-oriented learning; skills of independent work